Evaluating of Four Irrigation Depths on Soil Moisture and Temperature, and Seed Cotton Yield Under Film-Mulched Drip Irrigation in Northwest China - Xianghao Hou; Wenhui Hu; Quanqi Li; Junliang Fan; Fucang Zhang (Agronomy, 2025)
Soil mulching and irrigation are critical practices for alleviating water scarcity and enhancing crop yields in arid and semi-arid regions by regulating soil moisture and soil temperature. Clarifying the effects of various irrigation depths on soil moisture and temperature under mulched condition is essential for optimizing irrigation strategies. This study investigated the effects of four irrigation depths based on crop evapotranspiration (ETc): 60, 80, 100, and 120% (W0.6, W0.8, W1.0, and W1.2, respectively) on the soil moisture content (SMC), soil temperature and seed cotton yield in mulched cotton fields. Results revealed that when the irrigation depth increased from 60%ETc to 120%ETc, seed cotton yield increased by 12.04% in 2018 and 17.00% in 2019 at the cost of irrigation water use efficiency (IWUE), which decreased from 2.53 kg m−3 to 1.54 kg m−3 in 2018 and 2.60 kg m−3 to 1.58 kg m−3 in 2019. Soil temperature exhibited a temporal trend of initial increase followed by decline, and it was positively affected by soil mulching. Notably, W0.6 treatment maintained significantly higher soil temperature than other treatments. Soil moisture content was positively affected by irrigation depth, while soil water storage first decreased and then increased over time, reaching the minimum at the flowering and boll setting stages during the two growing seasons. Higher irrigation amount reduced the total spatial variability (C0 + C) of soil but did not significantly alter the distribution characteristics of soil moisture, as indicated by stable coefficients of variation (CVs) and stratification ratios (SRs). The variability of soil moisture diminished with soil depth with the lowest CV obtained at a 60 cm soil layer across the growth stages. Correlation analysis results showed that the seed cotton yield was mainly affected by irrigation depth and soil water storage. Soil temperature at the flowering and boll setting stage negatively affected seed cotton yield and was inversely correlated with soil water storage. The structural equation model (SEM) further indicated that both soil water storage and soil temperature primarily influenced seed cotton yield boll weight rather than boll number. Furthermore, 100%ETc (W1.0) can be considered as the recommended irrigation depth based on the soil moisture and temperature, seed cotton yield and water use efficiency in this region.